New text steganography method using the arabic letters dots - Ahlam R. Khekan; Hiba Mohammed Wajeh Majeed; Omer F. Ahmed Adeeb (Indonesian Journal of Electrical Engineering and Computer Science, 2021)
With the increasing technological and electronic development, methods have been developed to hide important information using text steganography as a new technology, since it is not noticeable and easy to send and receive. The use of the Arabic language is one of the new methods used to hide data. In this work, we preview our method that depends to use the part of Arabic language properties to embed the secret English message in to cover text to create text steganography. More than half of the Arabic characters contain dots. Several characters have upper dots and others have lower dots. Some have one dot others have two dots. Few have even three dots. In this new idea, we will use the dots of charters to embed the English secret message. First, we will compress the secret message by using the 5-Bit Encoding (T-5BE) to make the cover text able to embed more bits of the secret message by 37.5%. Then we start using the Arabic semantic dictionary to correct the hiding path and enhancement the stego-cover text to eliminate errors caused by switching words. In this research, we were able to extract experimental results that show that the proposed model achieves high masking accuracy in addition to the storage capacity of the cover text.